2009
DOI: 10.3208/sandf.49.777
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Properties of Granular Materials Having Different Particle Shapes in Direct Shear

Abstract: The viscous properties of air-dried relatively poorly-graded granular materials having diŠerent particle shapes were evaluated by performing a series of direct shear (DS) tests. The applied loading histories include repeated step changes in the shear displacement rate (• s) or repeated sustained loading stages during otherwise monotonic loading (ML) at a constant • s under constant vertical stress. Test results of an angular gravelly soil (i.e., Chiba gravel-a) obtained from the present study and those of a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Figure 3 shows good agreement between values of R for some soils as calculated by Yoshimoto et al (2012) and the SAGI number, while Figure 4 shows that SAGI is also compatible with the Roundness factor proposed by Krumbein & Sloss (1969), as reported by Cho et al (2006). Finally, similar compatibility is observed with the values of degree of angularity as proposed by Lees (1964) for some soils reported in previous studies (Duttine & Tatsuoka, 2009), as shown in Figure 5. However, while the SAGI values were calculated from data based on many thousands of particles tested by the laser image analysis, the roundness measurements from all these previous studies were made on a much more limited number of particles (typically between 20-30).…”
supporting
confidence: 78%
“…Figure 3 shows good agreement between values of R for some soils as calculated by Yoshimoto et al (2012) and the SAGI number, while Figure 4 shows that SAGI is also compatible with the Roundness factor proposed by Krumbein & Sloss (1969), as reported by Cho et al (2006). Finally, similar compatibility is observed with the values of degree of angularity as proposed by Lees (1964) for some soils reported in previous studies (Duttine & Tatsuoka, 2009), as shown in Figure 5. However, while the SAGI values were calculated from data based on many thousands of particles tested by the laser image analysis, the roundness measurements from all these previous studies were made on a much more limited number of particles (typically between 20-30).…”
supporting
confidence: 78%
“…Regarding strain rate effects, granular soils exhibit very abundant and various effects. This was investigated by Tatsuoka et al (2002Tatsuoka et al ( , 2008, Di Benedetto et al (2002), Duttine and Tatsuoka (2009), Enomoto et al (2009) and Peng et al (2010). Different stress responses resulting from a sudden change of the strain rate are classified as 1.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying soil-pile behaviour has been interpreted as a consequence of the interplay between several factors, such as the breaking down of arching effects during creep, the activation of dilation enhancing the shaft capacity, the alteration of the grain structure due to chemical reactions, and the extensive crushing around the pile. [8][9][10] While the time-dependent characteristics of soils compressed at low pressure have been explored in many experimental studies, [11][12][13][14] other experimental works have focused on the effect of fragmented particles on the time-dependent characteristics of granular assemblies. 15,16 These studies have covered a wide range of experiments at different scales in which both the single particle [17][18][19] and the collective sample behaviour have been investigated.…”
Section: Introductionmentioning
confidence: 99%